A hydrogen bond-based self-repairing-conductive self-diagnosing fiber composite material and a preparation method thereof
By constructing a multi-level conductive network and a multi-hydrogen bond system, the system achieves accurate damage identification and room-temperature self-repair of fiber composite materials, solving the problems of inaccurate positioning of damaged areas and low repair efficiency in existing technologies. It is applicable to fields such as aerospace and wind turbine blades.
Patent Information
- Application Number
- CN202511083178.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2026-08-25
- Estimated Expiration
- 2045-08-04
AI Technical Summary
Existing fiber composite materials cannot accurately locate and identify the damaged area before repair, resulting in poor self-healing effect. Furthermore, the self-sensing function has certain limitations and cannot achieve accurate real-time location and repair of damage in complex environments.
A multi-level conductive network is constructed using hydroxylated multi-walled carbon nanotubes, graphite powder, chopped carbon fibers, and acrylamide. Combined with a multi-hydrogen bond system, damage is accurately identified through changes in resistivity and capacitance, and self-repair is achieved at room temperature.
It achieves highly sensitive self-diagnosis and room-temperature self-repair of fiber composite materials, significantly extending service life, reducing maintenance costs, and improving repair efficiency, and is applicable to aerospace, wind turbine blades and other fields.
Smart Images

Figure CN121005842B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis and its preparation method, belonging to the technical field of intelligent diagnostic and self-healing fiber-reinforced resin matrix composite materials and their preparation. Background Technology
[0002] Fiber-reinforced polymer (FRP) composites possess advantages such as lightweight, high strength, corrosion resistance, and fatigue resistance, and have been widely used in aerospace, marine energy, and civil engineering fields in recent years. FRP consists of a fiber-reinforcing phase, a resin matrix connecting phase, and a fiber / resin interface. However, the resin matrix is primarily composed of brittle, high-temperature resistant epoxy resin or a thermoplastic resin system prone to microcracks. During service, FRP is subjected to various harsh environments (such as extreme temperatures and intense radiation in space) and complex loads (static, cyclic fatigue, and impact). For example, when a satellite encounters space debris during flight, multi-scale and multi-type damage inevitably occurs within it (such as fiber-resin interface debonding, resin matrix cracking, fiber breakage, and interlaminar delamination). This micro-scale damage gradually expands, leading to sudden macroscopic failure, severely impacting the structural reliability, safety, and service life.
[0003] Non-destructive testing techniques (such as computed tomography, acoustic emission, and thermal imaging) can be used to detect internal damage in fiber-reinforced polymer (FRP) composites, but they suffer from drawbacks such as high equipment costs, unsuitability for online monitoring, and small sample size. Self-sensing technology for in-situ damage in composites based on resistance changes has low maturity and faces theoretical and technical bottlenecks related to material functionalization design and accurate damage assessment. Furthermore, existing self-healing technologies for FRP composites have issues with feasibility and applicability, particularly their inability to accurately identify and repair damage, posing significant scientific and technological challenges in practical structural applications. Therefore, achieving self-sensing of internal damage in FRP under harsh service environments and complex loads, and enabling in-situ self-repair to restore its service performance, presents a significant challenge to the safety, reliability, and long service life of FRP engineering structures. In the prior art, CN117264401B discloses a method for preparing basalt fiber composite materials with damage self-sensing and temperature-sensitive behavior. This invention improves the electrical properties of the composite material and endows it with damage self-sensing and temperature-sensitive behavior by grafting carbon nanotubes and reduced graphene oxide onto the surface of basalt fibers, then extruding the filaments using a single-screw extruder and fabricating the basalt fiber composite material using 3D printing. CN114414107B discloses a high-strength carbon fiber composite material with self-sensing function and its preparation method. A piezoelectric nanolayer of barium titanate nanomaterials is loaded onto a carbon fiber braided layer. The carbon fiber braided layer with the piezoelectric nanolayer is then used as an intermediate functional layer to construct a sandwich-structured conductive composite material. The self-sensing function of the carbon fiber composite material is achieved by detecting a sensitive and observable piezoelectric signal. CN115746503B discloses an electromagnetic wave-driven self-healing fiber-reinforced resin matrix composite material and its preparation method. It uses multi-walled carbon nanotubes and graphite as microwave absorbers to induce the movement of charges in the material to generate current. When there are defects such as cracks and pitting, the resistance is too high. When the current flows, Joule heating is generated, which melts the low-melting-point thermoplastic repair agent polycaprolactone and penetrates into the defect area to fill the damaged cracks or passivate the cracks. This achieves self-repair of the damage and can also enhance the mechanical properties of the damaged area. CN113817290B discloses a shrinkage-resistant self-healing epoxy resin / microcapsule composite material and its preparation method. The composite material includes epoxy resin, a curing agent, and shrinkage-resistant self-healing microcapsules. The shrinkage-resistant self-healing microcapsules are constructed from polymeric materials and include a core material and a wall material. The core material includes polymeric monomers, expanding monomers, and a thermo-photoinitiating system. The wall material includes urea-formaldehyde resin doped with a thermo-photosensitive shielding agent. The expanding monomers are mixed with polymeric monomers that do not shrink in volume after curing and have good electrical insulation properties. After thermo-photoinitiated polymerization and curing, the overall volume expands slightly to achieve the purpose of shrinkage-resistant self-healing of damage defects in epoxy resin insulation materials.
[0004] However, in the existing technologies, fiber composite materials cannot accurately locate and identify the damaged area before damage repair, resulting in the inability to achieve timely self-healing of internal damage. In particular, the added microcapsules / microcatheters and functional particle systems have irreversible damaging effects on the mechanical properties of the raw materials, easily causing stress concentration, reducing mechanical properties, and making the damage repair process slow and inefficient. In addition, the self-sensing function of the above composite materials has certain limitations, such as a high rate of missed detection of micron-level damage (pores, delamination), and the inability to accurately locate internal cracks in real time; the damage repair lacks autonomy and the repair response is sluggish, especially requiring specific external triggering conditions (high temperature, high pressure, electromagnetic wave drive) to stimulate the internal repair agent material to penetrate and fill the damaged area, resulting in the inability of the material to effectively repair damage in complex environments and applications. Summary of the Invention
[0005] In order to address the aforementioned defects in existing fiber composite materials, this invention provides a fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis, and its preparation method.
[0006] The technical solution of the present invention: One objective of this invention is to provide a fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis. This fiber composite material comprises the following components by mass parts: 0.1-1.0 parts hydroxylated multi-walled carbon nanotubes, 10-20 parts anhydrous ethanol, 10-20 parts acetone, 0.1-1 parts PVP, 1-3 parts silane coupling agent, 10-20 parts graphite powder, 5-10 parts chopped carbon fibers, 60-80 parts unidirectional fiber cloth, 1-3 parts acrylamide, 2-4 parts PEI, and 80-120 parts epoxy resin curing system.
[0007] Further specified, the hydroxylated carbon nanotubes have a diameter of 8–50 nm and a length of 10–50 μm.
[0008] Further specifying, the mesh size of the graphite powder is 2000-3000 mesh.
[0009] Further specified, the length of the short-cut carbon fibers is 80-200 μm, and the diameter is 7 μm.
[0010] Further specified, the acrylamide particle size is 10–30 μm.
[0011] Further specifying, the molecular weight of PEI is 1200–1800 g / mol.
[0012] Further specifying, the silane coupling agent is KH550.
[0013] Further specifying, the unidirectional fiber cloth is made of carbon fiber, glass fiber, basalt fiber, or plant fiber.
[0014] Furthermore, when the unidirectional fiber cloth is made of carbon fiber, glass fiber or basalt fiber, desizing treatment is required before spraying, and then the desizing fiber is acidified to achieve carboxylation or hydroxylation of the fiber surface.
[0015] The second objective of this invention is to provide a method for preparing the above-mentioned fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis, the method comprising the following steps: (1) Hydroxylated multi-walled carbon nanotubes and silane coupling agent were added to anhydrous ethanol and ultrasonically dispersed to obtain mixed solution I; (2) After adding PVP to mixed solution I and stirring to dissolve it, short-cut carbon fibers and graphite powder are added in sequence, and after ultrasonic stirring to make them uniform, mixed solution II is obtained. (3) Add acrylamide and PEI to acetone and stir evenly to obtain mixed solution III. Add mixed solution II to mixed solution III and ultrasonically disperse evenly to obtain mixed solution IV. Continue to add a portion of epoxy resin from the epoxy resin curing system, ultrasonically disperse, and high-speed shear to obtain mixed solution V. (4) Place the mixed solution V in an oil bath at 80~120℃, heat and stir for 4~6 hours, and add a portion of the curing agent in the epoxy resin curing system after the solvent has completely evaporated to obtain adhesive solution VI; (5) Apply a portion of the adhesive VI evenly to both sides of the unidirectional fiber cloth by brushing, and place it in an oven at 40~80℃ for 1~4 hours to obtain the modified fiber cloth; (6) Add the remaining adhesive solution VI to the epoxy resin in the remaining epoxy resin curing system, stir evenly, add the curing agent in the remaining epoxy resin curing system, and treat evenly to obtain adhesive solution VII. (7) The adhesive VII and the modified fiber cloth are prepared by vacuum infusion or molding process to obtain a fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis.
[0016] The third objective of this invention is to provide a self-diagnostic method for the above-mentioned fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis. This self-diagnostic method is to infer the location of strain abrupt changes in the damaged area of the fiber composite material by detecting the changes in resistivity and capacitance inside the fiber composite material and its specific surface.
[0017] The fourth objective of this invention is to provide a self-healing method for the above-mentioned fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis. The self-healing method involves placing the damaged fiber composite material under normal temperature, low temperature below 60°C, or electromagnetic wave conditions to achieve self-healing of the fiber composite material.
[0018] Beneficial effects: (1) This invention utilizes a micro-nano multi-level conductive filler composed of carbon nanotubes, micron-sized sheet graphite powder, and unidirectional short-cut carbon fibers to construct a quantum tunneling effect and a three-dimensional conductive framework. Even if there is no direct contact between the micron-level conductive fillers (graphite powder and short-cut carbon fibers), the uniform dispersion and high conductivity of the carbon nanotubes will generate a quantum effect due to wave properties, leading to the tunneling effect through the potential barrier, thus ensuring the formation of a stable conductive network. Furthermore, when the fiber composite material is subjected to external loads, the conductive fillers are rearranged due to the external force, causing changes in the contact state of the conductive fillers; changes in the spacing between the conductive fillers lead to changes in the tunneling effect; and changes in the fiber structure caused by external forces... Local deformation of the fiber composite material causes changes in the intrinsic resistivity of the conductive filler; the pull-out behavior of the conductive filler under tension / compression causes changes in the contact resistivity between the conductive filler and the resin matrix; and due to the ionic conductivity of the fiber composite material, the fibrous / sheet-like conductive phase (short-cut carbon fiber / graphite powder) can be regarded as a capacitor plate. The changes in the distance and relative permittivity of the capacitor plate caused by external force lead to changes in capacitance, ultimately causing changes in the resistivity of the fiber composite material. Furthermore, by accurately identifying the changes in electrical properties of the fiber composite material under stress, the location of damage can be determined based on the electromechanical correspondence, and a self-sensing function can be provided, achieving precise damage localization (error < 1 mm²). Further, a multi-reversible hydrogen bond system is utilized, consisting of amide groups (CONH2) in acrylamide, amino groups (-NH2) and hydroxyl groups (-OH) in polyethyleneimine and carbon nanotubes, and ester groups (COOR) in epoxy resin. Hydrogen bonds, as weak, dynamically reversible non-covalent bonds, have a bond energy only one-half that of carbon-carbon covalent bonds (approximately 400 kJ / m²). Polymers containing hydrogen bonds (kJ / mol) readily break and reform at room temperature, thus exhibiting room-temperature self-healing properties. The acrylamide used in this application contains both hydrogen acceptor carbonyl groups and hydrogen donor amine groups, providing multiple carriers for achieving a sufficient number of hydrogen bonds. Polyethyleneimine and carbon nanotubes also provide a large number of amino and hydroxyl groups, respectively. This provides a strong force for the self-assembly of proton donors (NH) and proton acceptors (C=O, OH) to form multiple hydrogen bonds, while simultaneously providing abundant crosslinking points for the polymer network. This allows for rapid recombination at the fracture interface, thereby achieving polymer network reconstruction. Self-healing units are formed by dynamic covalent bonds, achieving the self-healing effect of the composite fiber material. Experimental results show that a self-healing efficiency of >90% is achieved at room temperature. Furthermore, the dynamic and directional nature of multiple hydrogen bonds makes fiber composites a core mechanism for balancing material stiffness and repair capability.
[0019] (2) The fiber composite material provided by this invention breaks through the limitations of traditional material diagnosis and repair separation, forming a closed-loop intelligent response system. Compared with traditional materials, it also has the following three core advantages: First, the multi-level conductive network endows the material with high-sensitivity self-diagnosis capability, accurately identifying different damage mechanisms such as fiber breakage, resin cracking, and interface debonding through resistivity / capacitance changes, significantly extending the service life of the composite material; Second, the design of multiple hydrogen bonds (amide group (CONH2), amino group (-NH2), hydroxyl group (-OH)) realizes targeted self-healing, dynamically reorganizing the cross-linked network at the damage interface, and achieving damage self-repair at room temperature under complex working conditions. It is also suitable for low-temperature repair below 60℃ or electromagnetic wave accelerated repair, enabling efficient maintenance of in-service components, significantly shortening the maintenance cycle, and reducing material waste and environmental pollution. Thirdly, it has strong process compatibility (vacuum infusion / molding), reduces energy consumption by 30% and retains strength ≥95%, extending material life by 2-3 times while reducing maintenance costs by 40%. It provides a breakthrough solution for the application of intelligent composite materials in aerospace, wind turbine blades, engineering structures and other fields. Moreover, the preparation conditions are mild, the process is simple and economical, and it shows broad industrial application prospects while achieving a low-cost, low-energy, and high-efficiency repair process.
[0020] (3) The fiber composite material provided by this invention uses very little additive, ensuring that the composite material has excellent mechanical strength (mechanical reinforcing phase: chopped carbon fibers, carbon nanotubes) and a three-dimensional conductive network (conductive phase: chopped carbon fibers, carbon nanotubes, graphite powder) structure. This achieves low additive content and endows the composite material with excellent mechanical properties and damage repair (multiple hydrogen bond carriers: acrylamide, polyethyleneimine, resin matrix, etc.). At the same time, through the closed-loop mechanism of "precise diagnosis of conductive network → targeted repair of dynamic hydrogen bond recombination", the intelligent perception of damage and in-situ self-healing function of fiber composite material are integrated for the first time. Attached Figure Description
[0021] Figure 1 This is a diagram illustrating the self-healing mechanism of the fiber composite material prepared in this invention; Figure 2 SEM image of the damaged area of the fiber composite material prepared in Comparative Example 1 before repair; Figure 3 SEM images of the damaged area after repair of the fiber composite material prepared in Comparative Example 1; Figure 4 SEM images of the damaged area of the fiber composite material prepared in Example 3 before repair; Figure 5 The image shows a SEM image of the damaged area after repair of the fiber composite material prepared in Example 3. Detailed Implementation
[0022] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0023] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art may make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0024] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0025] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.
[0026] The silane coupling agent used in the following examples and comparative examples is KH550; hydroxylated multi-walled carbon nanotubes, from Shenzhen Suiheng Graphene Technology, are 99% ultrapure with hydroxylation modification, 30 nm in diameter and 40 μm in length; the graphite powder has a particle size of 3000 mesh; the chopped carbon fibers have a length of 100 μm; the acrylamide has a particle size of 20 μm; the polyethyleneimine has a molecular weight of 1200 g / mol; the unidirectional carbon fiber cloth is a large-tow carbon fiber cloth: using a plain weave unidirectional braiding method; the bulk density is 1800 kg / m³. 3 The 100-part epoxy resin curing system includes 70 parts of bisphenol A type E51 epoxy resin and 30 parts of amine curing agent.
[0027] Example 1: The fiber composite material prepared in this embodiment comprises the following components in parts by mass: 0.1 parts hydroxylated multi-walled carbon nanotubes, 10 parts anhydrous ethanol, 10 parts acetone, 0.5 parts polyvinylpyrrolidone, 1 part silane coupling agent, 10 parts graphite powder, 5 parts chopped carbon fibers, 80 parts unidirectional carbon fiber cloth, 1 part acrylamide, 2 parts polyethyleneimine, and 100 parts epoxy resin curing system.
[0028] The method for preparing the fiber composite material in this embodiment is as follows: (1) Hydroxylated multi-walled carbon nanotubes and silane coupling agent were added to anhydrous ethanol and dispersed using an ultrasonic cell disruptor for 30 min to obtain mixed solution I; Ethanol is used to uniformly disperse carbon nanotubes to form a suspension. The dispersion mechanism involves the formation of silicon-oxygen covalent bonds between the silicon in the silane coupling agent and the oxygen in the hydroxylated carbon nanotubes. Simultaneously, the amino groups in the silane coupling agent dehydrate with the hydroxyl or carboxyl groups on the pretreated fiber surface to form NO or NC covalent bonds, thereby improving the fiber surface activity, mechanical properties, and roughness.
[0029] (2) After adding PVP to mixed solution I and stirring to dissolve it, short-cut carbon fibers and graphite powder are added in sequence, and the mixture is ultrasonically stirred for 3 hours to obtain mixed solution II. (3) Add acrylamide and PEI to acetone and stir evenly to obtain mixed solution III. Add mixed solution II to mixed solution III and ultrasonically disperse evenly to obtain mixed solution IV. Continue to add a portion of epoxy resin from the epoxy resin curing system, ultrasonically disperse, and high-speed shear to obtain mixed solution V. (4) Place the mixed solution V in a 100℃ oil bath and heat and stir for 5 hours. After the solvent has completely evaporated, add a portion of the curing agent in the epoxy resin curing system to obtain adhesive solution VI. (5) A portion of the adhesive VI was evenly coated on both sides of the unidirectional fiber cloth by brushing, and then placed in an oven at 60°C for 2 hours to obtain the modified fiber cloth. (6) Add the remaining adhesive solution VI to the epoxy resin in the remaining epoxy resin curing system, and mechanically stir at 3000 r / min for 60 min. After stirring evenly, add the curing agent in the remaining epoxy resin curing system and homogenize evenly with a homogenizer at 5000 r / min to obtain adhesive solution VII. (7) A fiber composite board based on hydrogen bond self-healing and conductive self-diagnosis was prepared by molding liquid VII and modified fiber cloth, named CFRP. The specific molding process is as follows: without pressure, the room temperature is raised to 160℃; the temperature is maintained at 160℃, the pressure is applied at 4 MPa and maintained for 30 min; the pressure is maintained and the temperature is cooled to room temperature.
[0030] Example 2: The difference between this embodiment and Embodiment 1 is that the prepared fiber composite material comprises the following components by mass parts: The mixture comprises 1 part hydroxylated multi-walled carbon nanotubes, 20 parts anhydrous ethanol, 20 parts acetone, 1 part polyvinylpyrrolidone, 3 parts silane coupling agent, 20 parts graphite powder, 20 parts chopped carbon fibers, 80 parts unidirectional carbon fiber cloth, 3 parts acrylamide, 4 parts polyethyleneimine, and 100 parts epoxy resin curing system. The method for preparing the fiber composite material is the same as in Example 1.
[0031] Example 3: The difference between this embodiment and Embodiment 1 is that the prepared fiber composite material comprises the following components by mass parts: The composition consists of 0.5 parts hydroxylated multi-walled carbon nanotubes, 15 parts anhydrous ethanol, 15 parts acetone, 0.5 parts polyvinylpyrrolidone, 1.5 parts silane coupling agent, 15 parts graphite powder, 7.5 parts chopped carbon fibers, 80 parts unidirectional carbon fiber cloth, 2 parts acrylamide, 3 parts polyethyleneimine, and 100 parts epoxy resin curing system. The method for preparing the fiber composite material is the same as in Example 1.
[0032] Comparative Example 1: The difference between this comparative example and Example 1 is that the prepared fiber composite material comprises the following components by mass: 80 parts unidirectional carbon fiber cloth and 100 parts epoxy resin curing system. The method for preparing the fiber composite material is the same as in Example 1.
[0033] Comparative Example 2: The difference between this comparative example and Example 1 is that the prepared fiber composite material comprises the following components by mass: 0.5 parts carbon nanotubes, 15 parts graphite powder, 7.5 parts chopped carbon fibers, 80 parts carbon fiber cloth, and 100 parts epoxy resin curing system. The method for preparing the fiber composite material is the same as in Example 1.
[0034] Comparative Example 3: The difference between this comparative example and Example 1 is that the prepared fiber composite material comprises the following components by mass: 2 parts acrylamide, 3 parts polyethyleneimine, 80 parts carbon fiber cloth, and 100 parts epoxy resin curing system. The method for preparing the fiber composite material is the same as in Example 1.
[0035] Electrical and mechanical properties of the fiber composite panels prepared in Example 3 and Comparative Examples 1-3 were tested. The specific pre-damage load was set to 80% of the ultimate load (flexural strength: 1426 MPa; short beam shear strength: 66 MPa). The mechanical property test was performed for 50 cycles. The samples were repaired after being left to stand at room temperature (25°C) for 6 hours after damage. The flexural strength, short beam shear strength and resistivity change rate of the samples before, after, and after damage were characterized.
[0036] The Fractional Change of Electrical Resistivity (FCR) is calculated by monitoring the change in resistance of carbon fiber composites under uniaxial tensile load and converting it into a measurement of the accuracy of their conductivity self-sensing performance.
[0037] The FCR value is calculated using the following formula: (1) (2) in, U The voltage (V) between the two internal electrodes; IThe current (A) passing through the CFRP specimen; A and L The areas of the electrodes (cm²) 2 ) and the distance (cm) between the two internal electrodes; ρ 0 and ρ The resistivity (Ω·cm) of the CFRP sample before and after loading are shown respectively.
[0038] Based on the characteristics of composite material repair, the damage introduced before repair is invisible impact damage, and the specimen is not completely damaged. Its repair efficiency is related to the strength after damage. Directly defining the repair efficiency as the ratio of the repaired strength to the original strength is inaccurate. Therefore, the self-healing efficiency η of the composite material is defined by the following formula: (3) The test results are shown in Table 1 below:
[0039] As shown in Table 1, the mechanical properties (flexural strength and short beam shear strength) of the fiber composite material prepared in Example 3 before and after damage are higher than those of Comparative Examples 1-3. This indicates that the synergistic effect between the functional fillers (mechanical reinforcement phase and damage repair phase) helps to improve the mechanical properties of the fiber composite material. It is worth noting that the addition of acrylamide and polyethyleneimine has a negative impact on the mechanical properties of the carbon fiber composite material (Comparative Examples 1 and 3), but the mechanical reinforcement phase can compensate for this effect by comparing it with Example 1. For example, compared with Comparative Example 1 before damage, the flexural strength and short beam shear strength of the Comparative Example 3 sample decreased by 11.0% and 6.1%, respectively, while the flexural strength and short beam shear strength of the Example 3 sample increased by 9.0% and 24.2%, respectively. In addition, the carbon fiber composite material (Example 3) that forms a three-dimensional conductive network under the same cyclic loading has the largest resistivity change rate fluctuation range, which is 24.6%, indicating that it has good conductivity and can accurately identify the damaged area inside the material. Furthermore, the damage repair efficiencies for bending strength in Example 3 and Comparative Examples 1-3 were 125.9% and 1.8% (negligible, no repair), 2.4% (negligible, no repair), and 67.0%, respectively, and the damage repair efficiencies for shear strength showed a similar trend.
[0040] Figure 1 This is a diagram illustrating the self-healing mechanism of the fiber composite material prepared in this invention, combined with... Figure 1This paper describes the self-healing mechanism of fiber composites. Hydrogen-bonded repair phases (acrylamide, polyethyleneimine) and conductive mechanical reinforcement phases (carbon nanotubes, chopped carbon fibers, graphite powder) are introduced into the resin matrix and fiber-resin interface. By monitoring the changes in resistivity, capacitance, and other electrical properties within and on the surface of the fiber composite, the location of strain abrupt changes in the damaged area can be inferred, enabling self-diagnosis. After identifying the damage location, multiple reversible hydrogen bonds will form in the acrylamide groups (CONH2) of acrylamide, the amino groups (-NH2) and hydroxyl groups (-OH) of polyethyleneimine and carbon nanotubes, and the ester groups (COOR) of epoxy resin, achieving efficient and targeted repair of repeated damage to the fiber composite.
[0041] Figures 2-5 These are microscopic morphology images of the fiber composite materials in Comparative Example 1 and Example 3 before and after self-healing of the damaged area: Figure 2 It can be seen that the fracture morphology of the sample in Comparative Example 1 after damage shows obvious microcracks, with crack sizes ranging from 4 μm to 10 μm; further, the fracture morphology after self-healing at room temperature for 6 hours is as follows. Figure 3 As shown, damage repair was not achieved. Figure 4 and Figure 5 The comparison shows that the fiber composite material in Example 3 exhibited obvious microcracks after damage. After 6 hours of self-healing at room temperature, the damaged areas between fibers were filled and bridged by functional fillers, demonstrating a significant repair effect. In summary, the composite material preparation and self-diagnosis / self-repair method provided by this invention can extend the service life of fiber composite materials, endow the materials with intelligent self-healing functionality, improve the healing response rate, select self-repair areas, and shorten the maintenance cycle. Furthermore, the preparation conditions are mild, the process is simple, economical, and has a wide range of applications.
[0042] The above description is only a preferred embodiment of the present invention. Given that those skilled in the art can make appropriate changes and modifications to the above embodiments, the present invention is not limited to the specific embodiments described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis, characterized in that, The fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis comprises the following components by mass parts: 0.1~1.0 parts hydroxylated multi-walled carbon nanotubes, 10~20 parts anhydrous ethanol, 10~20 parts acetone, 0.1~1 parts PVP, 1~3 parts silane coupling agent, 10~20 parts graphite powder, 5~10 parts chopped carbon fibers, 60~80 parts unidirectional fiber cloth, 1~3 parts acrylamide, 2~4 parts PEI, and 80~120 parts epoxy resin curing system; Preparation methods include: (1) Hydroxylated multi-walled carbon nanotubes and silane coupling agent were added to anhydrous ethanol and ultrasonically dispersed to obtain mixed solution I; (2) After adding PVP to mixed solution I and stirring to dissolve it, short-cut carbon fibers and graphite powder are added in sequence, and after ultrasonic stirring to make them uniform, mixed solution II is obtained. (3) Add acrylamide and PEI to acetone and stir evenly to obtain mixed solution III. Add mixed solution II to mixed solution III and ultrasonically disperse evenly to obtain mixed solution IV. Continue to add a portion of epoxy resin from the epoxy resin curing system, ultrasonically disperse, and high-speed shear to obtain mixed solution V. (4) Place the mixed solution V in an oil bath at 80~120℃, heat and stir for 4~6 hours, and add a portion of the curing agent in the epoxy resin curing system after the solvent has completely evaporated to obtain adhesive solution VI; (5) Apply a portion of the adhesive VI evenly to both sides of the unidirectional fiber cloth by brushing, and place it in an oven at 40~80℃ for 1~4 hours to obtain the modified fiber cloth; (6) Add the remaining adhesive solution VI to the epoxy resin in the remaining epoxy resin curing system, stir evenly, add the curing agent in the remaining epoxy resin curing system, and treat evenly to obtain adhesive solution VII. (7) The adhesive VII and the modified fiber cloth are prepared by vacuum infusion or molding process to obtain a fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis.
2. The method for preparing the fiber composite material according to claim 1, characterized in that, Hydroxylated carbon nanotubes have a diameter of 8–50 nm and a length of 10–50 μm.
3. The method for preparing the fiber composite material according to claim 1, characterized in that, The graphite powder has a mesh size of 2000-3000 mesh.
4. The method for preparing the fiber composite material according to claim 1, characterized in that, The chopped carbon fibers have a length of 80–200 μm and a diameter of 7 μm.
5. The method for preparing the fiber composite material according to claim 1, characterized in that, Acrylamide has a particle size of 10–30 μm.
6. The method for preparing the fiber composite material according to claim 1, characterized in that, PEI has a molecular weight of 1200–1800 g / mol.
7. The method for preparing the fiber composite material according to claim 1, characterized in that, The silane coupling agent is KH550.
8. A self-diagnostic method for a fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis prepared by the preparation method according to any one of claims 1 to 7, characterized in that, By detecting the changes in resistivity and capacitance within and on the specific surface of fiber composite materials, the location of strain abrupt changes in the damaged area of the fiber composite material can be inferred, thus achieving self-diagnosis.
9. A self-healing method for a fiber composite material based on hydrogen bond self-healing and conductive self-diagnosis prepared by the preparation method according to any one of claims 1 to 7, characterized in that, Damaged fiber composite materials can be placed under normal temperature, low temperature below 60°C, or electromagnetic wave conditions to achieve self-repair.
Citation Information
Patent Citations
Anti-shrinkage self-healing epoxy resin / microcapsule composite material and its preparation method
CN113817290B
A high-strength carbon fiber composite material with self-sensing function and its preparation method
CN114414107B
Electromagnetic wave driven self-repairing fiber-reinforced resin-based composite material and preparation method thereof
CN115746503B
Electromagnetic wave driven self-repairing type fiber reinforced resin-based composite material and preparation method thereof
CN115746503A
Self-healing repair fiber reinforced resin composite material based on graphene and preparation method thereof
CN117820808A